(untitled) (Economics and region, 2022)
The current state of renewable energy sources in Ukraine is studied. The growth rates of the introduction of alternative types of energy have been determined. Statistical data on the number of commissioned power plants and the amount of electricity produced by them had been analyzed. The issue of Ukraine`s investment potential for the development of the solar energy generation system taking into account the existing powerful solar power plants is considered. Geographical prospects of development of alternative energy on the territory of Ukraine from the point of view of export relations with the countries of the world were investigated. The indicators of the total capacity of solar energy of Ukraine were analyzed and the rating was determined in Europe by growth rates. Factors influencing the market of energy services, which contribute to the rapid pace of development of alternative energy were described. The advantages of commissioning solar power plants for private business were presented.